Large sample statistical estimation of streamflow sensitivity to climate and land cover change - Anderson, BJ (2023)
Some of the perennial questions in hydrology relate to how land cover change and precipitation affect streamflow change. These questions have been addressed in many ways over the years, but some common assumptions remain insufficiently challenged or addressed. The work presented in this thesis seeks to address some of these gaps using a large sample of observed hydrological, climatological, and land surface data. The increased availability of large-sample hydrological data in recent years and growing interest in the use of statistical models for causal inference with observed data have made it possible to conduct research which sheds light on patterns and drivers of hydrological non-stationarity, a topic that is a matter of increasing importance for the community.